Pemanfaatan Aplikasi M-JKN untuk Meningkatkan Efektivitas Pelayanan BPJS Kesehatan di Kantor Cabang Manokwari - Putriana, Ellen Bella; Tata, Jan F; Sudarwadi, Dirarini (Lensa Ekonomi, 2023)
The National Health Insurance (JKN) mobile application is a form of digital transformation of the business model of the Health Social Security Administration Agency (BPJS), which was originally in the form of administrative activities carried out at branch offices or health facilities, transformed into an application that can be used by participants anywhere and anytime. just without any time limit. The National Health Insurance (JKN) Mobile Application provides convenience for users or participants of the Health Social Security Administration (BPJS). The aim of this research is to determine the effectiveness of the services of the Health Social Security Organizing Agency (BPJS) at the Manokwari branch office. This type of research is descriptive research with a qualitative approach. This research took 3 sources as sources. Meanwhile, the data collection technique uses observation, interview and documentation techniques. The results of this research show that the effectiveness of services at the Health Social Security Administration (BPJS) through the National Health Insurance (JKN) Mobile application at the Manokwari branch office is said to be ineffective and inefficient because there are still many obstacles or problems in the application.